Impact of family security grants on household meal intake: Empirical evidence from senegal - Mussa Deme; Ghulam Dastgir Khan; Md Abdul Bari (Scientific African)
This paper investigates the impact of Family ecurity Grants, a form of cash transfer, training, and linkage to income-generating opportunities, on household food consumption in Senegal. Our focus is on daily meal intake, a key indicator of household welfare. Employing a fuzzy regression discontinuity design as an identification strategy, our results consistently reveal a significant increase in food consumption among households receiving these grants. This aligns with the program's overarching goals of alleviating food insecurity, eliminating hunger and poverty, and enhancing overall household well-being. The findings of this paper carry significant implications for policymakers, suggesting the need to broaden the program's reach to encompass a more substantial number of households and consider increasing grant amounts to strengthen its impact.